Challenging interest alignment: Frame analytic perspective on entrepreneurship education in higher education context. (March 2021) - Niska, Miira
Entrepreneurship promotion in higher education is a highly controversial issue. Yet entrepreneurship education is nowadays part of the education system all over Europe. In order to be legitimate, entrepreneurship education implemented in higher education institutions is expected to serve multiple stakeholders, among them society, students and faculty members. Yet previous studies have demonstrated that students and faculty members also object to entrepreneurship education. This article adopts a frame analytic perspective on entrepreneurship education and examines attempts to make sense of entrepreneurship education in a way that aligns various stakeholders' interests. The data analysed in the article consists of interviews ( N = 11) with people who implement entrepreneurship education in a Finnish university. The article calls for more research on university students' and graduates' relation to social entrepreneurship and entrepreneurial work life agency emphasized in the implementers' framings.